2020
DOI: 10.1101/2020.06.24.20131185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sentinel Coronavirus Environmental Monitoring Can Contribute to Detecting Asymptomatic SARS-CoV-2 Virus Spreaders and Can Verify Effectiveness of Workplace COVID-19 Controls

Abstract: Detecting all workplace asymptomatic COVID-19 virus spreaders would require daily testing of employees, which is not practical. Over a two week period, nine workplace locations were chosen to test employees for SARS-CoV-2 infection (841 tests) and high-frequency-touch point environmental surfaces (5,500 tests) for Coronavirus using Eurofins COVID-19 SentinelTM RT-PCR methods. Of the 9 locations, 3 had one or employees infected with SARS-CoV-2, neither of whom had symptoms at the time of testing nor developed s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Estimates of genome copies per cm 2 of SARS-CoV-2 RNA positive surface samples were calculated using a standard curve with no sample collected exceeding 6.6x10 3 genomic copies/cm 2 . While finding limited amounts of SARS-CoV-2 nucleic acid at sites reporting a COVID-19 cases may seem counter-intuitive, low levels of contamination were reported in similar studies including the in areas recently occupied by symptomatic workers (Gholipour et al, 2020;Marshall et al, 2020;Mouchtouri et al, 2020;Cherrie et al, 2021;Marcenac et al, 2021;de Rooij et al, 2023) and in some clinical settings occupied by infected patients (Ryu et al, 2020;Goel et al, 2022;Warren et al, 2022). Two control sites were also sampled as part of this study; both positive and suspected positive samples were identified at these sites albeit at lower levels than in recruited sites.…”
Section: Discussionmentioning
confidence: 85%
“…Estimates of genome copies per cm 2 of SARS-CoV-2 RNA positive surface samples were calculated using a standard curve with no sample collected exceeding 6.6x10 3 genomic copies/cm 2 . While finding limited amounts of SARS-CoV-2 nucleic acid at sites reporting a COVID-19 cases may seem counter-intuitive, low levels of contamination were reported in similar studies including the in areas recently occupied by symptomatic workers (Gholipour et al, 2020;Marshall et al, 2020;Mouchtouri et al, 2020;Cherrie et al, 2021;Marcenac et al, 2021;de Rooij et al, 2023) and in some clinical settings occupied by infected patients (Ryu et al, 2020;Goel et al, 2022;Warren et al, 2022). Two control sites were also sampled as part of this study; both positive and suspected positive samples were identified at these sites albeit at lower levels than in recruited sites.…”
Section: Discussionmentioning
confidence: 85%
“…High Ct-value shows lower viral load on the surface close to viral shedding. 17 Other references stated that Ct-value is not correlated directly or indirectly with the degree of severity. Ct-value can be opposite to the viral load and transmissibility.…”
Section: Methodsmentioning
confidence: 99%
“…Monitoring of SARS-CoV-2 on environmental surfaces could predict the presence of asymptomatic and pre-symptomatic personnel at the workplace (32,33). This could allow for response and control measures to be implemented for these personnel.…”
Section: -Virus Survives In the Food Establishment Environment And On Fomitesmentioning
confidence: 99%